Digital Accounting Adoption in Micro and Small Enterprises: The Roles of Accounting Training and Information Technology Access - Minanari, Minanari; Yessie, Afly; Aini, Lusia Sri (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2025)
Micro and small enterprises play a crucial role in economic resilience, yet many continue to face persistent challenges in maintaining systematic and reliable financial records. Limited accounting capacity and uneven access to information technology remain major barriers to the adoption of proper financial record-keeping practices. This study aims to examine the roles of accounting training and information technology access in influencing financial record-keeping practices among micro and small enterprises. Using a quantitative research design, primary data were collected through structured questionnaires from 50 micro and small enterprises operating in an urban area. The data were analyzed using validity and reliability tests, multiple linear regression, and hypothesis testing, including t-tests, F-tests, and the coefficient of determination. The results indicate that accounting training does not have a statistically significant effect on financial record-keeping practices, suggesting that training programs alone may not be sufficient to ensure consistent implementation. In contrast, access to and utilization of information technology show a significant positive effect on financial record-keeping practices, highlighting the critical role of digital tools in improving accuracy, efficiency, and consistency in financial reporting. Simultaneously, accounting training and information technology access jointly influence financial record-keeping practices, although technology access emerges as the dominant factor. These findings imply that policies and support programs for micro and small enterprises should prioritize expanding access to user-friendly digital accounting technologies while reorienting accounting training toward more practical, application-based approaches to enhance their effectiveness.